The paradox of sustainable innovation: the ‘Eroom’ effect (Moore’s law backwards) - Hall, Jeremy; Matos, Stelvia; Gold, Stefan; Severino, Liv S. (Elsevier, 2018)
Innovation has been widely acknowledged as a key mechanism for addressing sustainable development concerns. However, less attention has focused on downstream commercialization challenges such as achieving increasingly complex and stringent regulatory approval. Such challenges may hinder the development of more sustainable technologies, especially those coming from smaller or publically funded institutes. As well, they may obstruct the development of applications that could provide societal benefits, but may only have limited commercial viability due to small market niches or applicability to customers with limited financial means. We explore this apparent paradox using the concept of the Eroom effect (Moore’s Law backwards), i.e. where improved price performance due to technological advances are outweighed by increasing costs of regulatory approval and other commercialization costs. We illustrate this phenomenon with two cases of publically funded institutes, one developing transgenic cotton, and the other lignin transformation technology that can replace petroleum-based feedstocks in a number of industrial applications. We discuss the unintended consequences of the Eroom effect and conclude with implications for industry, policy and NGOs.